Phase equilibria in the ternary Ag-Au-Ga system: Isothermal sections at 250°C and 450°C - Jendrzejczyk-Handzlik D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The ternary Ag-Au-Ga system seems to be interesting in jeweller’s craft as a joint. Moreover, the ternary systems based on gold and silver have found applications in the dental industry. A literature overview of the Ag-Au-Ga system shows that the information about phase equilibria of this system does not exist. In the present work, phase equilibria in the Ag-Au-Ga ternary system have been studied by using scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS) analysis and X-ray diffraction analysis (XRD). Twenty two annealed alloys in the 10-70 at.% Ga region have been investigated. Obtained experimental results were compared with the predicted isothermal sections at two temperatures (250°C and 450°C). No ternary compounds are found.